Electrolytic capacitor, cathode body, and method for manufacturing an electrolytic capacitor

KR103032198B1Active Publication Date: 2026-10-13NIPPON CHEMI CON CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
KR1020237034302
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-06-22
Filing Date
2022-06-21
Publication Date
2026-10-13
Estimated Expiration
2042-06-21

Smart Images

  • Figure 112023109811627-PCT00003_ABST
    Figure 112023109811627-PCT00003_ABST
Patent Text Reader

Abstract

The present invention provides an electrolytic capacitor that suppresses a decrease in capacitance over time, a cathode body provided by the electrolytic capacitor, and a method for manufacturing the electrolytic capacitor. An electrolytic capacitor comprises an anode foil, a cathode body, and an electrolyte. The anode foil is made of valve metal and has a dielectric oxide film formed on the surface of the foil. The cathode body has a cathode foil of valve metal and a carbon layer laminated on said cathode foil. The interfacial resistance between the cathode foil and the carbon layer is 1.8 mΩ·cm² or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to an electrolytic capacitor, a cathode body provided by the electrolytic capacitor, and a method for manufacturing the electrolytic capacitor. Background Technology

[0002] An electrolytic capacitor is provided with an anode foil formed by forming a dielectric oxide film on a valve metal such as tantalum or aluminum, and a cathode foil made of the same or a different valve metal, positioned opposite each other. An electrolyte is interposed between the anode foil and the cathode foil. The electrolyte is interposed between the anode foil and the cathode foil, comes into close contact with the uneven surface of the anode foil, and functions as a true cathode.

[0003] Recently, electrolytic capacitors in which a solid electrolyte is interposed between the anode and cathode foils instead of an electrolyte are also widely used. Electrolytic capacitors equipped with this solid electrolyte are small, high-capacity, and have low equivalent series resistance, making them indispensable for the miniaturization and high-performance of electronic devices. Manganese dioxide and 7,7,8,8-tetracyanoquinodimethane (TCNQ) complexes are known as solid electrolytes. Furthermore, conductive polymers derived from monomers having π-conjugated double bonds are rapidly becoming popular as solid electrolytes. Examples of such conductive polymers include poly(3,4-ethylenedioxythiophene) (PEDOT). In conductive polymers, high conductivity is exhibited when polyanions such as organic sulfonic acids are used as dopants during chemical oxidation polymerization or electrolytic oxidation polymerization, and they also have excellent adhesion to dielectric oxide films.

[0004] However, compared to electrolytic capacitors equipped with liquid electrolytes, electrolytic capacitors equipped with solid electrolytes lack the repair function of defects in the dielectric oxide film. Therefore, so-called hybrid-type electrolytic capacitors, in which a solid electrolyte is interposed between the anode and cathode foils while liquid electrolyte is impregnated, are also attracting attention.

[0005] In electrolytic capacitors, not only is a dielectric oxide film intentionally formed on the anode foil, but an oxide film is also formed on the surface of the cathode foil due to reactions with air or the oxidizing action of the electrolyte. For this reason, an electrolytic capacitor can be regarded as a series capacitor in which capacitance, also known as Cap, is manifested on both the anode and cathode sides. In such electrolytic capacitors, it is important to ideally asymptotically extend the capacitance of the cathode side to infinity in order to efficiently extract the capacitance from the anode side.

[0006] Therefore, an electrolytic capacitor is proposed in which carbon is formed on the surface of a cathode foil using a dry plating method such as ion plating (see, for example, Patent Document 1). By preventing the intrusion of the electrolyte into the surface of the cathode foil and inhibiting the new formation and growth of the oxide film on the cathode foil, the capacitance exhibited on the cathode side is asymptotically close to infinity, thereby making the capacitance of the electrolytic capacitor only the anode capacitance. Prior art literature

[0007] [Patent Document 1] Japanese Patent Publication No. 2006-190878 The problem to be solved

[0008] However, simply forming a carbon layer on the cathode foil causes the capacitance of the electrolytic capacitor to degrade over a long period, and eventually, the rate of capacitance reduction falls below a limit, causing the electrolytic capacitor to reach the end of its lifespan.

[0009] The present invention is proposed to solve the above problem, and its purpose is to provide an electrolytic capacitor that suppresses the deterioration of capacitance over time, a cathode body provided by the electrolytic capacitor, and a method for manufacturing the electrolytic capacitor. means of solving the problem

[0010] As a result of the aforementioned research, the inventors obtained the following findings. That is, when a carbon layer is laminated onto a cathode foil, if the interfacial resistance between the cathode foil and the carbon layer is at least 1.8 mΩ·cm² or less, the rate of decrease in the capacitance of the electrolytic capacitor is suppressed to 30% or less compared to the initial state.

[0011] Based on this knowledge, in order to solve the above-mentioned problem, the electrolytic capacitor of the present invention is an electrolytic capacitor comprising an anode foil, a cathode body, and an electrolyte, wherein the anode foil is made of a valve metal and has a dielectric oxide film formed on the surface of the foil, and the cathode body has a cathode foil of the valve metal and a carbon layer laminated on the cathode foil, and the interfacial resistance between the cathode foil and the carbon layer is 1.8 mΩ·cm² or less.

[0012] In addition, as a result of the aforementioned research, the inventors obtained the following findings. Specifically, when a carbon layer is laminated onto a cathode foil, focusing on the interfacial resistance between the cathode foil and the carbon layer, the rate of decrease due to the deterioration of capacitance over time varied significantly with respect to at least 1.6 mΩ·cm². In fact, compared to when the interfacial resistance between the cathode foil and the carbon layer was about 1.63 mΩ·cm² or less, the deterioration of the capacitance of the electrolytic capacitor over time was well suppressed.

[0013] Based on this additional finding, the interfacial resistance between the cathode foil and the carbon layer may be 1.6 mΩ·cm² or less. .

[0014] The above cathode foil may have a surface expansion layer on its surface and the carbon layer on the surface expansion layer. If the surface expansion layer is formed in addition to the carbon layer, the cathode foil and the carbon layer adhere closely due to the anchoring effect caused by carbon entering the concave parts of the irregularities in the surface expansion layer, thereby making it easier for the interfacial resistance between the cathode foil and the carbon layer to be further reduced.

[0015] The carbon layer may be press-bonded to the cathode foil. In addition to forming the carbon layer, press-bonding the carbon layer to the cathode foil makes it easier to further lower the interfacial resistance between the cathode foil and the carbon layer. Furthermore, it is more preferable for the press-bonding of the carbon layer to the cathode foil and the formation of the expanded layer on the cathode foil to coexist. When the carbon layer is press-bonded to the cathode foil on which the expanded layer is formed, the carbon material of the carbon layer is pushed into the pores of the irregularities of the expanded layer, and the carbon layer is deformed along the irregular surface of the expanded layer, thereby further improving the adhesion and adhesion between the carbon layer and the cathode foil. For this reason, the interfacial resistance between the cathode foil and the carbon layer is more likely to be further reduced.

[0016] In addition, to solve the above-mentioned problem, the negative body of an electrolytic capacitor is also an embodiment of the present invention, and the negative body of the electrolytic capacitor comprises a negative foil and a carbon layer formed on the surface of the negative foil, and is characterized in that the interfacial resistance between the negative foil and the carbon layer is 1.8 mΩ·cm² or less.

[0017] The interface resistance between the above cathode foil and the above carbon layer may be 1.6 mΩ·cm² or less.

[0018] In addition, to solve the aforementioned problem, a method for manufacturing an electrolytic capacitor is also an embodiment of the present invention, and the method for manufacturing an electrolytic capacitor comprises a positive electrode foil, a negative electrode body, and an electrolyte, wherein a carbon layer is formed on a negative electrode foil of a valve metal, and then the carbon layer is pressed against the negative electrode foil by press processing until the interfacial resistance becomes 1.8 mΩ·cm² or less, thereby The method is characterized by including a cathode body fabrication process for fabricating a cathode body, a capacitor device fabrication process for fabricating a capacitor device by facing the cathode body fabricated by the cathode body fabrication process with the anode foil having a dielectric oxide film formed on its surface, and an impregnation process for impregnating the capacitor device with an electrolyte.

[0019] In the above cathode fabrication process, the carbon layer may be pressed against the cathode foil by press processing until the interfacial resistance becomes 1.6 mΩ·cm² or less. Effects of the invention

[0020] According to the present invention, the deterioration of the capacitance of an electrolytic capacitor over time can be suppressed. Brief explanation of the drawing

[0021] Figure 1 is a graph showing the relationship between interface resistance and the rate of change of capacitance (ΔCap). Specific details for implementing the invention

[0022] Hereinafter, an electrolytic capacitor and a manufacturing method according to an embodiment of the present invention will be described. Furthermore, the present invention is not limited to the embodiments described below.

[0023] (Overall composition)

[0024] An electrolytic capacitor is a passive component that obtains capacitance through the dielectric polarization action of a dielectric oxide film and performs the accumulation and discharge of electric charge through this capacitance. This electrolytic capacitor comprises an anode foil with a dielectric oxide film formed on its surface, a cathode, an electrolyte, and a separator. The anode foil and the cathode are arranged facing each other, and the separator and the electrolyte are interposed between the anode foil and the cathode. The anode foil and the cathode are arranged in a stacked type, alternately stacked with a separator in between, or in a wound type, wound with a separator in between. A solid electrolyte layer may be disposed between the anode foil and the cathode in addition to the electrolyte.

[0025] (Electrode)

[0026] The cathode body is equipped with a cathode foil. The anode foil and the cathode foil of the cathode body are foil bodies made of valve metal. The valve metal is aluminum, tantalum, niobium, niobium oxide, titanium, hafnium, zirconium, zinc, tungsten, bismuth, and antimony, etc. The purity is preferably 99.9% or higher for the anode foil and about 99% or higher for the cathode foil, but it may contain impurities such as silicon, iron, copper, magnesium, and zinc.

[0027] The anode foil and cathode foil have a surface layer having a surface structure formed on one or both sides of the foil. The surface layer is formed by electrolytic etching, chemical etching, sandblasting, etc., or by depositing or sintering metal particles, etc., onto the foil. That is, the surface layer is formed by tunnel-like pits, spongy pits, or voids between dense particles. Examples of electrolytic etching include DC etching or AC etching in which direct or alternating current is applied in an acidic aqueous solution containing halogen ions such as hydrochloric acid. In addition, in chemical etching, the anode foil and cathode foil are immersed in an acidic solution or an alkaline solution. Furthermore, the tunnel-like pits may be formed with a length that penetrates the foil, or may be formed with a length that is shorter than the center of the foil.

[0028] The dielectric oxide film on the anode foil is typically an oxide film formed on the surface layer of the anode foil. This dielectric oxide film is, for example, aluminum oxide formed by oxidizing the surface layer of the expanded layer if the anode foil is aluminum foil. The dielectric oxide film is intentionally formed by a chemical treatment in which voltage is applied in a solution free of halogen ions, such as an aqueous solution of adipic acid, boric acid, or phosphoric acid. On the surface layer of the cathode foil, an oxide film may also be intentionally formed by this chemical treatment, or an oxide film may be formed naturally. The natural oxide film occurring naturally on the surface layer of the cathode foil is formed by the cathode foil reacting with oxygen in the air.

[0029] (Cathode body)

[0030] The cathode body comprises a carbon layer in addition to the cathode foil. The carbon layer is laminated on the cathode foil. The carbon layer is a layer containing a carbon material. The carbon material is fibrous carbon, carbon powder, or a mixture thereof. It is preferable that the fibrous carbon or carbon powder undergo porous treatment, such as a regeneration treatment or an opening treatment to form holes.

[0031] Carbon powders include, for example, natural plant tissues such as coconut shells, synthetic resins such as phenol, activated carbon derived from fossil fuels such as coal, coke, or pitch, carbon black such as ketjen black, acetylene black, channel black, or thermal black, carbon nanohorns, amorphous carbon, natural graphite, artificial graphite, graphitized ketjen black, mesoporous carbon, etc. Fibrous carbons include, for example, carbon nanotubes, carbon nanofibers, etc. Carbon nanotubes may be single-layer carbon nanotubes in which a single layer of graphene sheet is formed, or multilayer carbon nanotubes (MWCNT) in which two or more layers of graphene sheet are arranged coaxially to form multiple layers of tube walls.

[0032] It is preferable that this carbon layer be formed such that the interface resistance between the carbon layer and the cathode foil is at least 1.6 mΩ·cm² or less. If this interface resistance is 1.6 mΩ·cm² or less, the rate of decrease in the capacitance of the electrolytic capacitor over time is suppressed to a low level. On the other hand, if this interface resistance exceeds 1.6 mΩ·cm², the rate of decrease in the capacitance of the electrolytic capacitor increases rapidly.

[0033] 1.6 mΩ·cm² The phenomenon in which the rate of decrease in capacitance over time changes significantly around the interface resistance is a conjecture and is not limited thereto, but is conjectured as follows. That is, the interface resistance between the carbon layer and the cathode foil is correlated with the diameter and volume of the pores between the carbon layer and the cathode foil. Furthermore, an interface resistance of 1.6 mΩ·cm² or less corresponds to a gap in diameter and volume where the electrolyte cannot enter between the carbon layer and the cathode foil, and thus cannot come into contact with the surface of the cathode foil. For this reason, when the interface resistance is 1.6 mΩ·cm² or less, the growth of the oxide film on the cathode foil is suppressed, and the cathode side is maintained in a high-capacity state. When the cathode side is maintained in a high-capacity state, the capacitance of the anode side can be efficiently and continuously drawn out, and the rate of decrease in capacitance over time of the electrolytic capacitor is suppressed to a low level.

[0034] However, when the interfacial resistance between the carbon layer and the cathode foil exceeds 1.63 mΩ·cm² and is 1.8 mΩ·cm² or less, the rate of decrease in the capacitance of the electrolytic capacitor increases rapidly, but the rate of decrease in the capacitance of the electrolytic capacitor is suppressed to 30% or less compared to the initial state. The initial state refers to the period before a load test under a high-temperature environment in which the electrolytic capacitor is exposed to a temperature environment of 125°C and a DC voltage of 2.4V is applied. Therefore, the interfacial resistance between the carbon layer and the cathode foil is kept at least 1.8 mΩ·cm² or less.

[0035] As a method for adjusting the interfacial resistance between the carbon layer and the cathode foil, press processing in which the carbon layer and the cathode foil are press-bonded is preferred. In press processing, the laminate of the carbon layer and the cathode foil is fitted into a press roller, and a linear press pressure is applied. The linear press pressure is preferably about 0.01 to 100 t / cm. In addition, the press temperature, which is the temperature of the press roller during pressing, is preferably about 0 to 200°C.

[0036] In addition, as a preliminary step to press processing, a carbon layer is formed on the cathode foil by vacuum deposition, sputtering, ion plating, CVD method, coating, electroplating, electroless plating, etc. In the case of coating, a carbon material is dispersed in a dispersion solvent to prepare a slurry, and the slurry is applied to and dried on the cathode foil by a slurry casting method, a doctor blade method, or a spray method. In the case of vacuum deposition, the carbon material is evaporated by heating it with an electric current in a vacuum, or by irradiating the carbon material with an electron beam in a vacuum to evaporate it, thereby forming a carbon material film on the cathode foil. In addition, in the case of sputtering, a target made of carbon material and the cathode foil are placed in a vacuum vessel, and an inert gas is introduced into the vacuum vessel and voltage is applied to cause the plasma-formed inert gas to collide with the target, thereby depositing carbon material particles emitted from the target onto the cathode foil.

[0037] In addition, to lower the interfacial resistance between the carbon layer and the cathode foil, it is desirable to intentionally form an oxide film of approximately 0.5V to 3V on the cathode foil through chemical treatment. The oxide film formed on the cathode foil has an effect that lowers the capacitance of the electrolytic capacitor, but it also has an effect that improves the adhesion between the carbon layer and the cathode foil. When a carbon layer is formed on a cathode foil having an oxide film of approximately 0.5V to 3V, the improvement in adhesion has a stronger effect compared to an oxide film outside this range, and the interfacial resistance between the carbon layer and the cathode foil is easily lowered to 1.6mΩ·cm² or less. Therefore, if an oxide film of approximately 0.5V to 3V is intentionally formed on the cathode foil, the effect of capacitance reduction caused by the oxide film is overcome, and the decrease in the capacitance of the electrolytic capacitor can be suppressed.

[0038] In addition, as a method for adjusting the interfacial resistance between the carbon layer and the cathode foil, forming a expanded layer on the surface of the cathode foil can be cited. By forming an expanded layer on the surface of the cathode foil as well, the carbon material of the carbon layer enters the irregularities of the expanded layer, thereby lowering the interfacial resistance between the carbon layer and the cathode foil. If the carbon layer and the cathode foil are press-processed after forming the expanded layer on the cathode foil, the interfacial resistance can be lowered even more easily.

[0039] In addition, as a method for adjusting the interfacial resistance between the carbon layer and the cathode foil, the selection of the carbon material contained in the carbon layer can be cited. As for the carbon material, spherical carbon black is preferred. By using spherical carbon black with a primary particle diameter of an average of 100 nm or less, the carbon layer becomes denser, and since the carbon layer adheres more easily to the expanded layer, the interfacial resistance tends to decrease.

[0040] In addition, the carbon material contained in the carbon layer may be flaky or scale-like graphite and carbon black, which is spherical carbon. It is preferable that the aspect ratio of the short axis to the long axis of the flaky or scale-like graphite be in the range of 1:5 to 1:100. When a carbon layer containing this combination of carbon material is laminated onto a cathode foil, the carbon layer is compressed, and then pressure-bonded to a expanded surface, the carbon black is easily coated onto the expanded surface by the graphite. The graphite is easily deformed along the uneven surface of the expanded surface, making it easy to laminate on the uneven surface. Furthermore, the graphite acts as a pressure lid, blocking the spherical carbon inside the expanded surface. Because of this, the interfacial resistance between the carbon layer and the cathode foil is easily reduced.

[0041] In addition, the interfacial resistance can be measured as follows. That is, the potential on the surface of the carbon layer of the cathode body, which has formed a carbon layer, is measured at multiple locations. The surface of the carbon layer where the potential is measured is, in other words, the surface located opposite to the surface in contact with the cathode foil, or the exposed surface of the cathode body. In measuring the potential, the resistance calculated when an application test needle is brought into contact with the surface of the carbon layer and a measurement test needle is also brought into contact with the surface of the carbon layer, and a predetermined DC current is applied between the test needles, is the "interfacial resistance at the cathode." As a preferred device for obtaining the interfacial resistance at the cathode, for example, the electrode resistance measurement system RM2610 manufactured by Hioki Denki Co., Ltd.

[0042] (Electrolyte)

[0043] The solvent of the electrolyte is water, a protonic organic polar solvent, or a non-protonic organic polar solvent, used alone or in combination of two or more types. The solute contains anionic and cationic components. The solute is typically a salt of an organic acid, a salt of an inorganic acid, or a salt of a complex compound of an organic acid and an inorganic acid, used alone or in combination of two or more types. The acid that becomes an anion and the base that becomes a cation may be added to the electrolyte separately as solute components.

[0044] Examples of protonate organic polar solvents include monohydric alcohols, polyhydric alcohols, and oxyalcohol compounds. Examples of monohydric alcohols include ethanol, propanol, butanol, pentanol, hexanol, cyclobutanol, cyclopentanol, cyclohexanol, and benzyl alcohol. Examples of polyhydric alcohols and oxyalcohol compounds include ethylene glycol, propylene glycol, glycerin, methylcellosolve, ethylcellosolve, methoxypropylene glycol, and dimethoxypropanol.

[0045] Representative examples of non-protonic organic polar solvents include sulfones, amides, lactones, cyclic amides, nitriles, and sulfoxides. Examples of sulfones include dimethylsulfone, ethylmethylsulfone, diethylsulfone, sulfolane, 3-methylsulfolane, and 2,4-dimethylsulfolane. Examples of amides include N-methylformamide, N,N-dimethylformamide, N-ethylformamide, N,N-diethylformamide, N-methylacetamide, N,N-dimethylacetamide, N-ethylacetamide, N,N-diethylacetamide, and hexamethylphosphoricamide. Examples of lactones and cyclic amides include γ-butyrolactone, γ-valerolactone, δ-valerolactone, N-methyl-2-pyrrolidone, ethylene carbonate, propylene carbonate, butylene carbonate, isobutylene carbonate, etc. Examples of nitrile-based compounds include acetonitrile, 3-methoxypropionitrile, glutaronitrile, etc. Examples of sulfoxide-based compounds include dimethyl sulfoxide, etc.

[0046] Examples of organic acids include oxalic acid, succinic acid, glutaric acid, pimetic acid, souveric acid, sebacic acid, phthalic acid, isophthalic acid, terephthalic acid, maleic acid, adipic acid, benzoic acid, toluic acid, enantic acid, malonic acid, 1,6-decanedicarboxylic acid, 1,7-octanedicarboxylic acid, azelaic acid, undecanedic acid, dodecaneedic acid, tridecaneedic acid, carboxylic acids, phenols, and sulfonic acids. In addition, examples of inorganic acids include boric acid, phosphoric acid, phosphorous acid, hypophosphorous acid, carbonic acid, and silicic acid. Examples of complex compounds of organic and inorganic acids include borodisalicylic acid, borodioxalic acid, and borodiglyglycolic acid.

[0047] Examples of at least one salt of these organic acids, inorganic acids, and complex compounds of organic and inorganic acids include ammonium salts, quaternary ammonium salts, quaternized amidinium salts, amine salts, sodium salts, potassium salts, etc. Examples of quaternary ammonium ions of quaternary ammonium salts include tetramethylammonium, triethylmethylammonium, tetraethylammonium, etc. Examples of quaternized amidinium include ethyldimethylimidazolinium, tetramethylimidazolinium, etc. Examples of amines of amine salts include primary amines, secondary amines, and tertiary amines. Examples of primary amines include methylamine, ethylamine, propylamine, etc. Examples of secondary amines include dimethylamine, diethylamine, ethylmethylamine, dibutylamine, etc. Examples of tertiary amines include trimethylamine, triethylamine, tripropylamine, tributylamine, ethyldimethylamine, ethyldiisopropylamine, etc. In the electrolyte, it is preferable to add an ion-dissociable salt having an anionic component which is one of these organic acids, inorganic acids, or complex compounds of organic and inorganic acids, and a cation component which is one of these bases.

[0048] In addition, other additives may be added to the electrolyte. Examples of additives include polyethylene glycol, complex compounds of boric acid and polysaccharides (mannitol, sorbitol, etc.), complex compounds of boric acid and polyhydric alcohols, boric acid esters, nitro compounds, phosphate esters, colloidal silica, etc. These may be used individually or in combination of two or more types. Nitro compounds suppress the generation of hydrogen gas within the electrolytic capacitor. Examples of nitro compounds include o-nitrobenzoic acid, m-nitrobenzoic acid, p-nitrobenzoic acid, o-nitrophenol, m-nitrophenol, p-nitrophenol, etc.

[0049] After preparation, this electrolyte is impregnated into a capacitor element. The capacitor element is formed by facing an anode foil having a dielectric oxide film and a cathode body having a carbon layer laminated on a cathode foil through a separator. When impregnating the capacitor element with the electrolyte, depressurization or pressurization may be performed as necessary to promote impregnation. The impregnation process may be repeated multiple times. Additionally, when a solid electrolyte layer is used in combination, the electrolyte is impregnated into a capacitor element having a solid electrolyte layer.

[0050] The solid electrolyte layer contains a conductive polymer. The conductive polymer is a conjugated polymer or a doped conjugated polymer. Conjugated polymers are obtained by chemical oxidation polymerization or electrolytic oxidation polymerization of monomers having π-conjugated double bonds or derivatives thereof. By performing a doping reaction on the conjugated polymer, the conductive polymer exhibits high conductivity.

[0051] As conjugated polymers, known ones may be used without particular limitation. Examples include polypyrrole, polythiophene, polyfuran, polyaniline, polyacetylene, polyphenylene, polyphenylenevinylene, polyacene, polythiophenevinylene, etc. As a conductive polymer, a representative example is poly(3,4-ethylenedioxythiophene), called PEDOT, which is doped with polystyrenesulfonic acid (PSS). These conjugated polymers may be used alone, in combination of two or more types, or as copolymers of two or more monomers.

[0052] The dopant may be any known one without specific limitations. Examples include inorganic acids such as boric acid, nitric acid, and phosphoric acid, and organic acids such as acetic acid, oxalic acid, citric acid, ascotine, tartaric acid, squaric acid, rhodizonic acid, croconic acid, salicylic acid, p-toluenesulfonic acid, 1,2-dihydroxy-3,5-benzenedisulfonic acid, methanesulfonic acid, trifluoromethanesulfonic acid, borodisalicylic acid, bisoxalateborate, sulfonylimide, dodecylbenzenesulfonic acid, propylnaphthalenesulfonic acid, and butylnaphthalenesulfonic acid. In addition, polyanions may be used as dopants, and examples of polyanions include polyvinylsulfonic acid, polystyrenesulfonic acid, polyallylsulfonic acid, polyacrylsulfonic acid, polymethacrylic sulfonic acid, poly(2-acrylamide-2-methylpropanesulfonic acid), polyisoprenesulfonic acid, polyacrylic acid, polymethacrylic acid, polymaleic acid, etc. Dopants may be used alone or in combination of two or more types. In addition, polymers or monomers may be used.

[0053] A solid electrolyte layer is formed by impregnating a capacitor element with a dispersion in which a conductive polymer is dispersed. As the solvent for the dispersion, any solvent in which particles or powders of the conductive polymer are dispersed is sufficient, and water is mainly used. If necessary, ethylene glycol may be used as the solvent for the dispersion. It has been found that using ethylene glycol as the solvent for the dispersion can reduce the electrical properties of the product, particularly the ESR characteristics. To improve the impregnation and conductivity of the dispersion, various additives may be used in the dispersion, or neutralization may be performed by adding cations.

[0054] As a method for impregnating the capacitor element with a dispersion of a conductive polymer, the capacitor element may be immersed in the dispersion, or applied via drip coating or spray coating. Additionally, the capacitor element may be assembled after impregnating not only the entire electrode pair but also the anode foil or cathode body with the dispersion. To promote the impregnation of the dispersion into the electrode pair, reduced pressure or increased pressure treatment may be performed as necessary. This attachment process may be repeated multiple times.

[0055] In addition, the solid electrolyte layer may be formed by known electrolytic polymerization or chemical polymerization methods. In chemical polymerization, the solid electrolyte layer is formed by a method in which a capacitor element is impregnated with a solution in which a monomer and an oxidizing agent are dissolved in a solvent and then dried, or by alternately impregnating a pair of electrodes with a solution in which a monomer is dissolved in a solvent and a solution in which an oxidizing agent is dissolved in a solvent, and then drying. For example, a solid electrolyte is formed by using 3,4-ethylenedioxythiophene as the polymerizable monomer and an alcohol solution (such as ethanol) of ferric p-toluenesulfonic acid as the oxidizing agent, immersing a capacitor element in a mixture of the polymerizable monomer and the oxidizing agent, and causing a polymerization reaction of a conductive polymer by heating. In addition, a washing treatment may be performed before and after this heating treatment to remove unreacted monomers or excess monomers by washing with water.

[0056] In electrolytic polymerization, a solid electrolyte layer is formed by introducing a capacitor element into an electrolytic polymerization solution containing at least a monomer, a supporting electrolyte, and a solvent, and applying a voltage between an anode and a cathode. As the electrolytic polymerization solution, a monomer that becomes conductive through electrolytic polymerization may be used. Thiophene monomer or pyrrole monomer is preferred as the monomer. When using these monomers, the capacitor element is immersed in an aqueous solution for electrolytic polymerization containing the monomer and sodium 1-naphthalenesulfonate, which is the supporting electrolyte, inside a stainless steel container, and a predetermined voltage is applied. Accordingly, a solid electrolyte layer formed by a water-soluble monomer (e.g., thiophene or pyrrole) through electrolytic polymerization can be uniformly formed.

[0057] (Separator)

[0058] Examples of separators include cellulose such as kraft, Manila hemp, Esparto, hemp, and rayon, and mixtures thereof; polyester resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and derivatives thereof; polytetrafluoroethylene resins; polyvinylidene fluoride resins; vinylon resins; polyamide resins such as aliphatic polyamides, semi-aromatic polyamides, and fully aromatic polyamides; polyimide resins; polyethylene resins; polypropylene resins; trimethylpentene resins; polyphenylene sulfide resins; acrylic resins; and polyvinyl alcohol resins, and these resins may be used alone or in combination.

[0059] In addition, this separator is responsible for maintaining the solid electrolyte layer and the electrolyte, and preventing short circuits between the anode foil and the cathode. If the solid electrolyte layer can maintain its shape without the separator, maintain the additional electrolyte of the capacitor element containing the solid electrolyte layer, and have a thickness sufficient to prevent short circuits between the anode foil and the cathode, then the separator is not required.

[0060] (Manufacturing method)

[0061] Such electrolytic capacitors are manufactured through an anode foil fabrication process for producing an anode foil, a cathode body fabrication process for producing a cathode body, a device fabrication process for producing a capacitor element in which the anode foil and the cathode body are arranged facing each other, a solid electrolyte layer formation process for forming a solid electrolyte layer on the capacitor element, and an electrolyte impregnation process for impregnating the capacitor element with the formed solid electrolyte layer with an electrolyte.

[0062] In the process of manufacturing the anode foil, the valve metal is stretched to form the anode foil, and after forming a expanded layer on the anode foil, a dielectric oxide film is formed on the surface of the expanded layer. In the process of manufacturing the cathode, the valve metal is stretched to form the cathode foil, and an expanded layer is formed on the cathode foil. In addition, in the process of manufacturing the cathode, a carbon layer is formed on the cathode foil, and the carbon layer is pressed against the cathode foil by press processing, and the interfacial resistance between the carbon layer and the cathode foil is 1.8 mΩ·cm² or less, preferably 1.6 mΩ·cm² or less.

[0063] In the device fabrication process, an anode foil with a dielectric oxide film formed thereon and a cathode are overlapped through a separator. In the case of a stacked type, the anode foil, cathode, and separator are alternately stacked in multiple layers. In the case of a wound type, the anode foil and cathode overlapped through the separator are wound. In the solid electrolyte layer formation process, a dispersion solution containing a dispersed conductive polymer is impregnated into the capacitor element. In the electrolyte impregnation process, the electrolyte is impregnated into the capacitor element, which has a solid electrolyte layer formed by undergoing the solid electrolyte layer formation process.

[0064] Accordingly, an electrolytic capacitor is manufactured in which the interface resistance between the cathode foil and the carbon layer is 1.8 mΩ·cm² or less or 1.6 mΩ·cm² or less. This electrolytic capacitor suppresses the decrease in capacitance over time.

[0065] [Example]

[0066] Hereinafter, the electrolytic capacitor and manufacturing method of the present invention will be described in more detail based on the embodiments. Furthermore, the present invention is not limited to the following embodiments.

[0067] An electrolytic capacitor was fabricated as follows. First, aluminum foil was used as the cathode foil. The aluminum foil was subjected to AC etching treatment, and an expanded layer formed by spongy etching pits was formed on both sides of the foil. For the AC etching treatment, the cathode foil was immersed in an acidic aqueous solution with a liquid temperature of 25°C and approximately 8 wt% hydrochloric acid as the main electrolyte, and an AC of 10 Hz and a current density of 0.14 A / cm² Current was applied to the substrate for about 5 minutes, and both sides of the aluminum foil were expanded.

[0068] Next, a phosphating treatment was performed on the aluminum foil, and an oxide film was formed on the surface of the expanded layer. In the phosphating treatment, chlorine attached during the AC etching treatment was removed with an aqueous phosphoric acid solution, and then a voltage was applied in an aqueous solution of ammonium dihydrogen phosphate.

[0069] For the carbon layer of the cathode, carbon black was selected as the carbon material. A slurry was prepared by mixing and kneading carbon black powder, styrene-butadiene rubber (SBR) as a binder, and an aqueous solution of sodium carboxymethylcellulose (CMC-Na) as a dispersant.

[0070] This slurry was uniformly applied to the cathode foil. Then, the slurry was heated and dried to volatilize the solvent, and then press processing was performed on the cathode body. During the press processing, the cathode body was inserted into a press roller, and a linear press was applied to fix the carbon layer onto the cathode foil.

[0071] In addition, aluminum foil was used as the anode foil. On the aluminum foil, a surface layer formed by spongy etching pits was formed on both sides of the foil. In the AC etching treatment, the cathode foil was immersed in an acidic aqueous solution with a liquid temperature of 25°C and approximately 8 wt% hydrochloric acid as the main electrolyte, and an AC current of 10 Hz and a current density of 0.14 A / cm² was applied to the substrate for approximately 5 minutes. In addition, a phosphating treatment was performed on the anode foil to form a dielectric oxide film on the surface of the surface layer of the anode foil. In the phosphating treatment, chlorine attached during the AC etching treatment was removed with an aqueous phosphoric acid solution, and then a voltage was applied in an aqueous solution of adipic acid.

[0072] An aluminum tub-shaped lead terminal was ultrasonically connected to each of the anode foil and the cathode. Then, a zigzag separator was prepared, and the cathode and anode foil were alternately inserted into each bent section to face each other through the separator, thereby fabricating a laminate of the cathode, anode foil, and separator. Regenerated cellulose fibers were used as the separator. Additionally, the laminate was secured with imide tape to prevent it from opening.

[0073] The laminate was impregnated with an electrolyte. The electrolyte was prepared by using γ-butyrolactone as a solvent and tetramethylimidazolinium phthalate as a solute. After impregnating with the electrolyte, the laminate was encapsulated in a laminate material. Accordingly, an electrolytic capacitor of a laminate cell was fabricated. Aluminum with a thickness of 110 μm was used as the laminate material. After fabricating the laminate cell, an aging treatment was performed. During the aging treatment, a voltage of 3.35 V was applied for 60 minutes at a temperature of 105°C.

[0074] Multiple such electrolytic capacitors were manufactured. The interface resistance between the carbon layer and the cathode foil of each electrolytic capacitor is different by varying the press conditions for pressing the carbon layer against the cathode foil. The press line pressure, press temperature, and interface resistance of the cathode foil for each electrolytic capacitor are shown in Table 1 below.

[0075]

[0076] (Dosage test)

[0077] The over-time degraded capacitance of each electrolytic capacitor having the various interface resistances shown in Table 1 was measured. To measure this capacitance, the electrolytic capacitors were exposed to a temperature environment of 125°C and a DC voltage of 2.4V was applied. The initial capacitance before applying the DC voltage of 2.4V under the 125°C temperature environment and the capacitance after 750 hours were measured. The capacitance was measured by applying a 10kHz AC signal to the electrolytic capacitors. Then, the rate of change of capacitance (ΔCap) after 750 hours relative to the initial capacitance was calculated.

[0078] The results of the capacitance calculation are shown in Table 2 below. In addition, the results of Table 2 are shown in the graph of Figure 1. Figure 1 is a graph showing the relationship between interface resistance and the rate of change of capacitance (ΔCap). In the graph shown in Figure 1, interface resistance is placed on the horizontal axis and the rate of change of capacitance (ΔCap) is placed on the vertical axis.

[0079]

[0080] As shown in Table 2 and Figure 1, when the interfacial resistance between the carbon layer and the cathode foil is 1.63 mΩ·cm² or less, it can be confirmed that the capacitance of the electrolytic capacitor is suppressed to a decrease of about 26% or less compared to the initial state, even when a load is applied for 750 hours under a high-temperature environment. On the other hand, when the interfacial resistance between the carbon layer and the cathode foil exceeds 1.80 mΩ·cm², it can be confirmed that the capacitance of the electrolytic capacitor decreases rapidly as the interfacial resistance increases. However, up to an interfacial resistance between the carbon layer and the cathode foil of 1.80 mΩ·cm², it can be confirmed that the rate of decrease in the capacitance of the electrolytic capacitor is suppressed to 30% or less compared to the initial state.

[0081] Accordingly, it has been confirmed that the negative body of an electrolytic capacitor has a negative foil made of valve metal and a carbon layer laminated on said negative foil, and that the interfacial resistance between the negative foil and the carbon layer is at least 1.6 mΩ·cm² or less, even considering the error, thereby suppressing the decrease in capacitance over time. In particular, even though there is a concern that the rate of capacitance reduction may increase due to the oxide film when the adhesion between the negative foil and the carbon layer is improved by forming an oxide film of about 0.5 to 3 V on the negative foil, the decrease in capacitance can be suppressed even when an oxide film is formed on the surface of the negative foil by adjusting the interfacial resistance to 1.6 mΩ·cm² or less as in the present invention.

[0082] In addition, it was confirmed that the negative body of the electrolytic capacitor has a negative foil made of valve metal and a carbon layer laminated on the negative foil, and that the interfacial resistance between the negative foil and the carbon layer is at least 1.8 mΩ·cm² or less, even considering errors, and that the decrease in capacitance over time is suppressed to 30% or less compared to the initial state.

Claims

Claim 1 An electrolytic capacitor comprising an anode foil, a cathode body, and an electrolyte, wherein the anode foil is made of valve metal and has a dielectric oxide film formed on the surface of the foil, and the cathode body has a cathode foil of valve metal, an oxide film of 0.5V to 3V on said cathode foil, and a carbon layer laminated on said oxide film, and the interfacial resistance between said cathode foil and said carbon layer is 1.6mΩ·cm² or less. Claim 2 delete Claim 3 An electrolytic capacitor according to claim 1, wherein the cathode foil has a widened layer on its surface and has a carbon layer on the widened layer. Claim 4 An electrolytic capacitor according to claim 1 or 3, characterized in that the carbon layer is press-bonded to the cathode foil. Claim 5 A cathode body for an electrolytic capacitor, comprising a cathode foil, an oxide film having a voltage of 0.5V to 3V on the cathode foil, and a carbon layer formed on the surface of the oxide film, wherein the interfacial resistance between the cathode foil and the carbon layer is 1.6mΩ·cm² or less. Claim 6 delete Claim 7 A method for manufacturing an electrolytic capacitor comprising an anode foil, a cathode body, and an electrolyte, comprising: a cathode body manufacturing process in which an oxide film of 0.5V to 3V is formed on a cathode foil of valve metal, and a carbon layer is formed on the oxide film, and then the carbon layer is pressed against the cathode foil by press processing until the interfacial resistance becomes 1.6mΩ·cm² or less; a capacitor element manufacturing process in which a capacitor element is manufactured by facing the anode foil having a dielectric oxide film formed on its surface to the cathode body manufactured in the cathode body manufacturing process; and an impregnation process in which an electrolyte is impregnated into the capacitor element. Claim 8 delete

Citation Information

Patent Citations

  • Electrode body, electrolytic capacitor having electrode body, and method for manufacturing electrode body

    KR1020210055679A